FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN CONSUMER NON-CYCLICALS - Ryan Filbert Antoni; Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to obtain empirical evidence regarding the effect of profitability, liquidity and firm size on capital structure in consumer non-cyclicals companies. The sampling technique used was purposive sampling. The sample data in this study were 90 sample data. This study uses secondary data that is processed using Eviews version 12. The results of the F test show that profitability, liquidity and firm size together have a significant effect on capital structure. The results of the t test show that firm size have a positive and significant effect on capital structure while profitability and liquidity has a negative and significant effect on capital structure.